Pengembangan Website Match Maker Startup dan Investor - Grace Levina Dewi (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
Indonesian startups are growing at a breakneck pace. When starting a business, finances are required to continue to develop the business, sustain it, and defend it against competition in the startup environment. One of the most crucial responsibilities in a business is that of an investor. Investors can help startups by providing financial assistance (investment). There are now only a handful sites for developers to market their startups as promotional material. This promotion can be used to promote startups (owned products) to a wider audience and gain investors' attention. The above-mentioned limits are the primary focus of website creation. The waterfall concept was used in the building of this website. The goal of creating this website is not only to serve as a promotional tool, but also to provide an opportunity for entrepreneurs to meet investors in an indirect manner and to make it easier for investors to analyze businesses with future potential. Compatibility, performance, and usability tests are all used in website development. Website development from the developer's perspective received a usability score of 91.86%, indicating that the website is very excellent, and website development for investors received a score of 79.85%, indicating that the website is good.